Pseudothrombocytopenia due to Platelet Clumping: A Case Report and Brief Review of the Literature. (4th December 2016) - Tan, Geok Chin; Stalling, Melissa; Dennis, Gretchen; Nunez, Maria; Kahwash, Samir B.
Abstract : Platelet clumping is a common laboratory phenomenon that complicates or precludes reporting of platelet count. It is often, but not always, a phenomenon commonly caused by the anticoagulant EDTA. Herein, we discuss a case of a 14-year-old girl who was found to have platelet clumping and discuss the work-up she underwent to investigate her pseudothrombocytopenia.